Dimensional Scaling and Failure Pattern of the Tensile Properties of Angle-Ply Thermoplastic Composites of Twaron Fiber/Polypropylene - Martin-Barrera, Cesar; Soberanis-Monforte, Genaro A.; Gonzalez-Chi, Pedro I. (Frontiers in Materials, 2018)
Thermoplastic multilayer composites with different fiber orientations per layer were prepared with polypropylene and aramid fibers as reinforcing material. The prepregs were prepared in a continuous impregnation system using the dry powder method in a fluidized bed. The specimens were laminated by compression molding, tensile tested and their fracture area was analyzed by microscopy. The mechanical performance of the laminates was influenced by the fiber orientation at the different layers. The fibers at 0° conferred high stiffness to the composite, limiting the maximum deformation and promoting failure. The laminates with 0º layers showed a fragile and sudden fracture oriented at 90° to the aplied load, even with low fiber content. The plies oriented at  45° balanced the stress and contributed to higher levels of deformation during the test due to fiber rotation towards the loading direction, also, no post-yield stiffening was found as in thermoset composites due to the ductile nature of the thermoplastic matrix; these layers limited the crack propagation in the transverse direction, canceling the in-plane shear stress. The fibers at 90° acted as filler due to poor interface and did not contribute to the improvement of the composite mechanical performance. The evidence shows no delamination in the materials due to the tenacious nature of the thermoplastic matrix, neither saw-toothed or plateau region was found in the stress-strain curves in contrast to thermoset laminates.